Pengaruh Penggunaan Ice Breaking terhadap Hasil Belajar PAIBP Kelas VII di SMPN 3 Lembah Gumanti - Firdani, Wulan Rahma; Alfurqan, Alfurqan (YASIN, 2025)
This study is motivated by the learning fatigue experienced by students, which negatively impacts their concentration and learning effectiveness, as well as student aspirations for the inclusion of ice breaking activities during lessons. The objective of this research is to examine the effect of ice breaking on students’ learning outcomes in the subject of Islamic Religious Education and Character Development for Grade VII at SMPN 3 Lembah Gumanti. A quantitative experimental method was employed, involving 47 students selected through purposive sampling. Data were collected through observation, tests (pretest and posttest), and documentation, and analyzed using a t-test. Descriptive results indicated an increase in the posttest average score for the experimental group (79.38) compared to the control group (75.22), while pretest scores were relatively similar (48.54 and 49.57, respectively). Classical assumption tests confirmed that the data were normally distributed and homogeneous. However, the hypothesis testing using an independent sample t-test yielded significance values around 0.177–0.178 (p > 0.05), indicating no statistically significant difference in learning outcomes between the experimental and control groups. Therefore, although there was a numerical increase in learning outcomes, the implementation of ice breaking activities did not have a statistically significant effect. The null hypothesis (H₀) is accepted, while the alternative hypothesis (H₁) is rejected.